Desenvolvimento de um biorreator rotativo para produção de enzimas celulolíticas por fermentação em estado sólido - Grajales Agudelo, Lina María [UNESP] (2014)
The main target of this thesis was to develop a rotating drum bioreactor to produce cellulolitic enzymes by solid-state fermentation, with the thermophilic fungus Myceliophtora thermophila I-1D3b cultivated in sugar cane bagasse and wheat bran. The project was developed in five steps. The first step consisted in the movement visualization of the mixture bagasse-bran, weight proportion 7:3, respectively, to assess the best operational conditions to the particle movement in face of the internal elements of the drum. This evaluation was performed in two equipments: a rotating-wall drum made of Plexiglas, 30cm diameter and 60cm length, with straight baffles, and a stainless-steel drum with internal agitation promoted by paddles, with similar dimensions to the previously described drum. In the former equipment an inner tube, immersed into the bed of particles, could be used, in order to simulate the insertion of air in the real bioreactor to be used in the fermentation process. In these experiments, the controlled variables were the rotation frequency and the filling degree, and the response variable was the number of rotations required to obtain radial and axial homogeneity of the particle concentrations. The results showed that the radial mixture was directly related the load of particles in the drum, and no dependence was observed on the rotation frequency. A quicker homogeneity was obtained using the paddle drum, although some agglomeration of the material was observed in the frontal region. The experiments carried out using the inner tube showed quite low particle velocities around the tube. The particle flow regime was distinct of any other reported in literature. The axial dispersion in the paddle drum was higher, although some concentration heterogeneity was observed, while for the wall-rotating drum the concentration was evenly uniform. The second step was to assess the water retention capacity by the particles, targeting homogeneous ...